Conformational Landscape and Properties of Psilocybin: A Computational Approach - Bhadoria P.; Ramanathan V. (My University, 2025)
The conformational manifold of psilocybin, a psychedelic molecule, was extensively explored using DFT method. Two most stable conformers were identified and the second most stable conformer was found to be 2.08 kcal/mol higher than the global minimum. The barrier of rotation between the two conformers was found to be 14.63 kcal/mol. The structural and spectroscopic parameters of both these conformers were similar. AIM (Atoms in molecule) calculation revealed very strong intramolecular H-bond interactions in both the conformers. The structural parameters of these two conformers significantly matched with the earlier reported crystal structure of psilocybin. Further properties of these conformers were investigated using FMO (Frontier molecular orbital), AIM (Atoms in molecule), ESP (Electrostatic potential) calculations. UV (Ultraviolet)-visible, IR (Infrared) and 1H-NMR (Proton nuclear magnetic resonance) spectra were also computed. All the predicted results matched exceedingly well with the earlier reported literature. © 2022 Wiley-VCH GmbH.